2013
DOI: 10.1371/journal.pone.0082357
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Plasma B-Type Natriuretic Peptide Levels after High-Pressure Post-Dilation following Coronary Stent Deployment

Abstract: ObjectiveTo evaluate the changes of plasma B-type natriuretic peptide(BNP) levels after high-pressure post-dilation following coronary stent deployment.MethodsA total of 173 patients undergoing percutaneous coronary intervention for the left anterior descending artery were enrolled into the study. All patients were divided into two groups: the conventional group and the post-dilation group. The plasma BNP, troponin I(TnI), myocardial band isoenzyme of creatine kinase(CK-MB) levels and the serum high sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The pathophysiological mechanisms of the SF-NR phenomenon, including ischemia-reperfusion injury, microvascular spasm, distal thromboembolism, endothelial dysfunction, and individual susceptibility, are complex. 16,[18][19][20] Inadequate epicardial coronary blood supply can result in endothelial cell dysfunction and interstitial edema of cardiomyocytes. This can compress the microvascular lumen and increase its stenosis, ultimately leading to the development of anatomical SF-NR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiological mechanisms of the SF-NR phenomenon, including ischemia-reperfusion injury, microvascular spasm, distal thromboembolism, endothelial dysfunction, and individual susceptibility, are complex. 16,[18][19][20] Inadequate epicardial coronary blood supply can result in endothelial cell dysfunction and interstitial edema of cardiomyocytes. This can compress the microvascular lumen and increase its stenosis, ultimately leading to the development of anatomical SF-NR.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive post-dilation during primary PCI may increase type B natriuretic peptide, troponin I and hypersensitive C-reactive protein levels, resulting in MVD and consequently increasing the risk of SF-NR. 20 However, a recent prospective observational study combining coronary physiology and intracoronary imaging showed that post-dilation in patients with STEMI is beneficial in increasing fractional flow reserve after PCI, with no significant effect on coronary microcirculation overall. 27 In this study, balloon post-dilation did not increase the risk of SF-NR.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study showed a significantly increased level of plasma B-type natriuretic peptide, a biomarker for heart failure, and troponin Ⅰ, a biomarker of myocardial injury, after stent postdilation. 4…”
mentioning
confidence: 99%
“…All patients with coronary artery disease undergoing PCI were included in that meta-analysis, including patients with stable coronary artery disease. e levels of troponin I and highly sensitive C-reactive protein were elevated after stent expansion, suggesting more myocardial damage and inflammation [37]. e primary lesion in patients with acute coronary syndrome is more unstable due to more necrotic cores and fewer fibrous fatty plaques than in patients with stable coronary artery disease [38]; the elevation of cardiac troponin occurs in lesions with a large necrotic core area and in lipid-rich lesions [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…erefore, the deployment of postdilation in patients with ACS will increase the risk of myocardial damage, which may be the reason for increased all-cause death in this meta-analysis. In addition, studies have shown that the levels of plasma B-type natriuretic peptide significantly increase following the postdilation, which is a biomarker of heart failure [37]. Long-term heart failure can also cause an increased death.…”
Section: Discussionmentioning
confidence: 99%